Modeling Classroom Behaviors in Software Agents - Gibson, David (IGI Global, 2009)
In order for a digital simulation to provide an artificial teaching environment there needs to be a computational model of the act of teaching interacting with software agents. The COVE model integrates Cognitive science models, the OCEAN model of psychology and OCC model of emotions, Visual-Auditory-Kinesthetic perception and the Environment (social and physical expectations) for learning. A context for the COVE agent model is provided by the How People Learn (HPL) theory of learning and Behaviorist-Cognitivist-Constructivist (BCC) instructional framework. This chapter presents design considerations for computationally modeling COVE to enable agents to possess the psychological, physical, cognitive, and social aspects of learning that enable the representation of behaviors of students in learning environments and to allow simulation of HPL-BCC theories of instruction and learning.